2001
DOI: 10.1063/1.1408272
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous thermal conductivity enhancement in nanotube suspensions

Abstract: We have produced nanotube-in-oil suspensions and measured their effective thermal conductivity. The measured thermal conductivity is anomalously greater than theoretical predictions and is nonlinear with nanotube loadings. The anomalous phenomena show the fundamental limits of conventional heat conduction models for solid/liquid suspensions. We have suggested physical concepts for understanding the anomalous thermal behavior of nanotube suspensions. In comparison with other nanostructured materials dispersed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

46
1,209
6
19

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 2,489 publications
(1,280 citation statements)
references
References 21 publications
46
1,209
6
19
Order By: Relevance
“…The model predicts the percolation of thermal conductivity with the volume fraction change of the second phase, and the percolation threshold depends on the size and the shape of the nanoparticles. The theoretical predictions are in agreement with the experimental results.(Some figures in this article are in colour only in the electronic version)Nanocomposites have a wide range of applications in the fields of optoelectronics, thermoelectrics, sensors, etc, due to their novel structure and properties [1][2][3], such as nonlinear optical properties of granular metal-dielectric composites [2] and the large enhancement of effective thermal conductivity of a fluid with the addition of a small amount of carbon nanotubes [3]. With continuous miniaturization of semiconductor and microelectronic devices, thermal transport and heat management problems have begun to attract a great deal of attention [4,5].…”
supporting
confidence: 79%
See 2 more Smart Citations
“…The model predicts the percolation of thermal conductivity with the volume fraction change of the second phase, and the percolation threshold depends on the size and the shape of the nanoparticles. The theoretical predictions are in agreement with the experimental results.(Some figures in this article are in colour only in the electronic version)Nanocomposites have a wide range of applications in the fields of optoelectronics, thermoelectrics, sensors, etc, due to their novel structure and properties [1][2][3], such as nonlinear optical properties of granular metal-dielectric composites [2] and the large enhancement of effective thermal conductivity of a fluid with the addition of a small amount of carbon nanotubes [3]. With continuous miniaturization of semiconductor and microelectronic devices, thermal transport and heat management problems have begun to attract a great deal of attention [4,5].…”
supporting
confidence: 79%
“…Studies have found that thermal conductivity of nanowires and thin films is size-dependent, it is lower than the corresponding bulk value [6]. However, there are not many theoretical studies on the thermal conductivity of nanocomposites, despite its importance in applications [1,3].The effective medium theory (EMT) is often used to study the physical properties of composites, such as dielectric constant [2], thermal conductivity and electrical conductivity [7]; the percolation of electrical conductivity is usually found, but there are few reports on the percolation of thermal conductivity. The role of interface thermal resistance (ITR) in the thermal conductivity of nanocomposites was emphasized in recent studies [8,9], which improves the theoretical results based on the EMT, but the related work seems to be discussed only for the dilute limit [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The hot solution inside the tank was agitated slowly at 1.3 rps. The flow rate of cold fluid was set 5 .…”
Section: Methodsmentioning
confidence: 99%
“…The study also found that the classical Shah equation failed to predict the heat transfer behavior of nanofluids 4 . The study used copper particles in water as the nanofluid and measured the convective heat transfer coefficient and friction factor of the nanofluid for turbulent flow and proposed a convective heat transfer correlation for the nanofluid heat transfer 5 .…”
Section: Introductionmentioning
confidence: 99%